Soppangheid for Kaaps: Power, creolisation and Kaaps Afrikaans - Willemse, Hein (Multilingual Margins: A journal of multilingualism from the periphery, 2018)
In this contribution, the dignity of speakers of Cape Afrikaans (Kaaps) is discussed with reference to the need for bi-dialectic tuition at school and Afrikaans poetry written in the Cape eye dialect. It is argued here that, besides Standard Afrikaans, a greater awareness of language varieties must be cultivated in education and the media so that learners develop the ability to control a variety of language registers. Further the manifestation of Kaaps, as eye dialect, is discussed at the hand of poetry examples. Here it is found that poets often stereotypically affirm topics in their poetry written in dialect format. The hope is expressed that the dignity of Kaaps Afrikaans in poetry can be attained with multiple rhetorical strategies. The soppangheid, dignity, of Kaaps is not only a linguistic issue, but can also serve as a confirmation of the dignity of all Afrikaans speakers.